2016
DOI: 10.1007/s00595-016-1435-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a new approach for creating a preperitoneal space in transabdominal preperitoneal repair inguinal hernia repair: using a sandwich approach

Abstract: The sandwich approach is feasible as another standard dissective procedure for TAPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…3 ). Similarly, Nagahisa et al [ 15 ] suggested that this part of the fascia should be incised. Our view of space separation and mesh placement is consistent with that of Mirilas et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Similarly, Nagahisa et al [ 15 ] suggested that this part of the fascia should be incised. Our view of space separation and mesh placement is consistent with that of Mirilas et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal CO 2 pressure was established as 10 mmHg during the procedure. We dissected the preperitoneal layer using the Sandwich approach, because it is feasible for patients with prominent adhesion and is able to be safely performed by young surgeons [ 2 ]. We dissected all the hernia sac and did not retract the transversalis fascia.…”
Section: Methodsmentioning
confidence: 99%
“…The onset of chronic postoperative inguinal pain is multifactorial and includes patient-related factors and technical factors (12)(13)(14). Among the technical factors are the repair technique, nerve handling, and type of prosthetic material and its fixation (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Intra‐abdominal CO 2 pressure was maintained at 10 mmHg during the procedure. All TAPP repairs employed the sandwich approach, in which a preperitoneal cavity was created for mesh replacement while all preperitoneal fascias were preserved . The lateral layers were equivalent to the retroperitoneal spermatic sheath , thus preventing any nerves from being touched during creation of the preperitoneal cavity.…”
Section: Methodsmentioning
confidence: 99%